Sono e percepção visuoespacial em trabalhadores de uma empresa petroquímica submetidos a esquemas de trabalho em turnos alternantes - Soares, Cibele Siebra (2013)
Shift work consists of an array of unusual work hours, such as evenings and weekends, and increasing workload, in order to meet the uninterrupted production, which leads to changes in the quality, duration and regularity of sleep. Research indicates that sleep alteration cause cognitive processes to become slower, unstable and prone to errors, leading to loss of cognitive functions such as visuospatial perception. In this sense, this research aimed to evaluate sleep quality and its relation to visuospatial perception in workers in alternating shifts. Participants were 21 panel operators in a petrochemical company, male, aged 19-53 years. All participants were subjected to schedules of alternating shifts (day and night) of 12 nonstop hours and data were collected from 10 workers who were assigned to the day shift and 11 workers assigned to the night shift. For the sleep evaluation were used the Sleep Diary, the Sleep Habits Questionnaire, the Chronotype Identification Questionnaire and the Pittsburgh Sleep Quality Index (PSQI). The visuospatial skills were assessed using the Rey Complex Figure Test and attention was assessed using a portable version of the Psychomotor Vigilance Task (PVT). The results showed that the general sample of workers obtained poor sleep quality on working days and good sleep quality during the work break. There was shortened sleep duration in the work week and appropriate duration in the work break. No losses were found in the workers visuospatiality, but the good quality of sleep during the work break was correlated to adequate visuospatial performance, for the day shift workers. The attention performance oscillated throughout the work hours, especially on the night shift. It is concluded that the alternating shifts work scheme can be detrimental to the sleep quality workers and a good sleep quality can contribute to a better visuospatial performance